Improved Crack Healing and High‐Temperature Oxidation Resistance of Ni/Al2O3 by Y or Si Doping. Issue 7 (8th April 2016) - Maruoka, Daisuke; Nanko, Makoto
Abstract : Recovery of mechanical strength was investigated for 5 vol% Ni/α‐Al2 O3 nanocomposites that had improved resistance to high‐temperature oxidation by doping with Y or Si (Ni/Al2 O3 ‐Y and Ni/Al2 O3 ‐Si). Surface cracks disappeared completely because of the oxidation product, NiAl2 O4 . The fraction of crack disappearance was comparable between Ni/Al2 O3 ‐Y and Ni/Al2 O3 ‐Si. The apparent activation energy of crack healing is similar to the grain‐boundary diffusion of Ni ions in an Al2 O3 matrix. The rate‐controlling process of crack healing is the grain‐boundary diffusion of cations in an internally oxidized zone (IOZ) of the Ni/Al2 O3 system. The bending strengths of the as‐sintered and as‐cracked Ni/Al2 O3 ‐Y samples were 561 and 232 MPa, respectively. Heat treatment at 1200°C for 6 h resulted in a recovery of the bending strength up to 662 MPa for Ni/Al2 O3 ‐Y as well as 606 MPa for Ni/Al2 O3 ‐Si. Y and Si dopants were segregated into the Al site at the Al2 O3 grain boundaries, and then, enhanced covalent bonding occurred with neighboring oxygen. While the flux of Ni ions was retarded slightly by doping with Y and Si, a shorter IOZ provided enough Ni ions to form NiAl2 O4 on the surface. Ni/Al2 O3 ‐Y and Ni/Al2 O3 ‐Si have the desirable properties of crack healing and resistance to high‐temperature oxidation.